Gender Differences in HIV and Hepatitis C Related Vulnerabilities Among Aboriginal Young People Who Use Street Drugs in Two Canadian Cities - For the Cedar Project Partnership (Women Health, 2008)
OBJECTIVES: Vulnerability to HIV and Hepatitis C virus (HCV) infection for indigenous populations worldwide must be contextualized in experiences of current and past trauma. Aboriginal women entrenched in poverty face further gender-specific harms which place them at increased risk for HIV infection. METHODS: This study was cross-sectional and based on a community-based sample of Aboriginal young people (Métis, Aboriginal, First Nations, Inuit, and non-status Indians) between the ages of 14 and 30 years who used injection or non-injection non-cannabis illegal drugs (street drugs) in the previous month. Between October 2003 and July 2005, 543 participants living in either Vancouver or Prince George, Canada, were recruited by word of mouth, posters, and street outreach. Young people in the study completed a questionnaire administered by Aboriginal interviewers. Female participants (n = 262) were compared to male participants (n = 281) with respect to sociodemographics, trauma, sexual risk variables, and drug use patterns. Trained nurses drew blood samples for HIV and HCV antibodies and provided pre- and post-test counseling. RESULTS: Proportions positive for HIV and HCV were significantly higher among young women. HIV was 13.1% [9.5, 17.7] in women compared to 4.3% [2.5, 7.4] in men, and HCV was 43.6% [37.6, 49.8] in women as compared to 25.4% [20.5, 30.9] in men. When the analysis was restricted to young people who reported injection drug use, the proportions positive for HIV and HCV remained significantly higher among young women. Experiences of forced sex were reported by 70% of young women compared to 29% of young men, p < 0:001, while the median age of first forced sex was 6-years-old for both men and women. DISCUSSION: The results of the final model indicated that HIV had been associated with residing in Vancouver, having injected for longer, and sexual abuse, but not being female. However, this gendered analysis demonstrated that a greater proportion of young women were experiencing sexual abuse, and sexual abuse was associated with HIV positive status. Harm reduction and drug treatment programs are urgently required that target women at a young age and address complex traumatic experiences associated with childhood sexual abuse.